What about clonidine for diarrhoea? A systematic review and meta-analysis of its effect in humans - Fragkos, Konstantinos C.; Zárate-Lopez, Natalia; Frangos, Christos C. (Therapeutic advances in gastroenterology, 2016)
Background: Clonidine is considered an alternative treatment for refractory diarrhoea. The evidence in the literature is scarce and not conclusive. The present paper’s purpose is to gather available evidence and provide a systematic answer regarding the effectiveness of clonidine for diarrhoea. Method: We performed a systematic review of clonidine and its effect on diarrhoea. Meta-analysis was performed with a random effects model of the standardized mean difference (SMD) or the weighted mean difference and heterogeneity was quantified with I2 and publication bias was assessed with Egger’s and Begg’s test. Subgroup analyses and meta-regression were performed to investigate sources of heterogeneity. Any empirical study describing use of clonidine for diarrhoea in humans independent of age was included. For the meta-analysis, papers had to provide sufficient data to produce an effect measure, while case reports were not included in the meta-analysis and are discussed narratively only. Results: A total of 24 trials and seven case reports were identified. Clonidine (median dose 300 μg/day) has been used for treatment of diarrhoea in irritable bowel syndrome, faecal incontinence, diabetes, withdrawal-associated diarrhoea, intestinal failure, neuroendocrine tumours and cholera; studies were also performed on healthy volunteers. Results indicate a strong effect of clonidine on diarrhoea (SMD = −1.02, 95% confidence interval [CI] −1.46 to −0.58) with a decrease of stool volume by 0.97 l/day, stool frequency by 0.4 times/day and increase in transit time by 31 minutes. In a sensitivity analysis of studies with functional diarrhoea and sample size over 10 subjects, the effect was similar −0.99 (95% CI −1.54 to −0.43). There is however significant heterogeneity and publication bias. Heterogeneity decreased in subgroup analyses by condition but not with other factors examined. A limitation of the present study includes small study effects. Conclusion: Clonidine is effective for treatment of diarrhoea and should be considered as an alternative when all other medications have failed.